(untitled) (Sains Humanika, 2018)
Hadeeth studies is one of the important series studies in formal or informal courses of study in mosques. Some of the popular hadeeth works in this field that have been written either in Arabic or in Malay have been identified and used by most teachers in the peninsular, such as the work of Hadeeth, 40 Imam al-Nawawi, Riyadh al-Salihin, Mastika Hadith, Tajzib al-Atraf li al-Hadith, Bustanul Arifin, Hadith 40 Penawar Hati and so on. In delivering a study conducted, the form or method of deciphering the hadith study known as ilm syarah al-hadith should be followed by instructors in this study. This is because, some of the most important hadeeth rules have been compiled by ulama’ hadeeths in fact able to complete the studies of hadeeths. As a result, this paper will clarify the importance of knowledge of syarah al-hadith in understading hadith by Prophet Muhammad SAW. Among other objectives, it is also to analyze some of the methods of hadeeth lectures applied by the instructors, especially in the study of hadeeth conducted around the Daerah Muallim in the state of Perak Darul Ridzuan. This study also reveals the strengths and weaknesses of the hadeeth methodology used by some instructors in this field.